Grandezas e medidas no ciclo de alfabetização: suas tecituras em currículos prescritos de matemática - Vece, Janaina Pinheiro (2020)
This thesis is the result of a research on applied work whose approach is qualitative and based on documental type. The target is to investigate the setting of the Axis Quantities and Measures in the Cycle of Literacy in the prescribed Curricula of Mathematics. Thus, two methodological procedures were applied to its development:: biographical research (GIL 2002) to build the theoritical foundation and historical review about the presentation of the Axis Quantities and Measures in Mathematics curricula and the analysis of the content (BARDIN, 2016) to investigate the theme in the Common National Curriculum Basis (BRASIL, 2017) and in the elaborated curricula in its attendance. City Curriculum (SÃO PAULO, 2019) and Paulista Curriculum (SÃO PAULO, 2019). The theoritical foundation goes beyond the intrasciplinary, interdisciplinar and utilitarian characteristics. The axis of Quantities and Measures has several layers woven by procedures that vary from a continous quantity to another. In relation to the historical review, it shows in the state network of São Paulo, initially, the theme Measures was shared with the field of Science, becoming exclusive in the Mathematics Curriculum at the end of the 80´ies, consolidating itself in the Brazilian scenario by means of the publication of the National Curriculum Parameters of Mathematics (BRASIL, 1997). The results reveal that in the City Currriculum (SÃO PAULO, 2019) and in the Paulista Curriculum (SÃO PAULO, 2019), the setting of the axis Quantities and Measures, in the Cycle of Literacy, was associated with the process of interpretation and adaptation of continuous quantities such as length, mass, capacity, time , value and area.It also highlights important implication related to multiple characteristics of the theme , for instance, the exclusive treatment attributed to quantities , time and value as well as the concentration of quantities of distinct origins – length, mass and capacity – in the description of the same objects of knowledge (contents) and abilities (essential learning).